2018
DOI: 10.1007/s00394-018-1630-4
|View full text |Cite
|
Sign up to set email alerts
|

Intake of dietary saturated fatty acids and risk of type 2 diabetes in the European Prospective Investigation into Cancer and Nutrition-Netherlands cohort: associations by types, sources of fatty acids and substitution by macronutrients

Abstract: Purpose The association between dietary saturated fatty acids (SFA) intake and type 2 diabetes (T2D) remains unclear. This study aimed at investigating the association between SFA intake and T2D risk based on (1) individual SFA (differing in carbon chain length), (2) food sources of SFA and (3) the substituting macronutrients. Methods 37,421 participants from the European Prospective Investigation into Cancer and Nutrition-Netherlands (EPIC-NL) cohort were included in this study. Baseline dietary intake was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 44 publications
5
27
0
1
Order By: Relevance
“…Meat is a source of SFA and dietary cholesterol, but neither total dietary SFA [43], nor dietary cholesterol [44] have been associated with increased risk of T2DM in recent studies. Those conclusions were contrary to results obtained in the study by Guess et al [45] in which researchers compared the intake of fatty acids between normoglycaemic participants, prediabetes participants and participants with type 2 diabetes, and provided observation that increased consumption of saturated fatty acids was associated not only with higher risk of impaired fasting glucose and higher concentration of glucose after 2h in OGTT (Oral Glucose Tolerance Test), but also with insulin resistance.…”
Section: Meat Fish Eggsmentioning
confidence: 99%
“…Meat is a source of SFA and dietary cholesterol, but neither total dietary SFA [43], nor dietary cholesterol [44] have been associated with increased risk of T2DM in recent studies. Those conclusions were contrary to results obtained in the study by Guess et al [45] in which researchers compared the intake of fatty acids between normoglycaemic participants, prediabetes participants and participants with type 2 diabetes, and provided observation that increased consumption of saturated fatty acids was associated not only with higher risk of impaired fasting glucose and higher concentration of glucose after 2h in OGTT (Oral Glucose Tolerance Test), but also with insulin resistance.…”
Section: Meat Fish Eggsmentioning
confidence: 99%
“…On the other hand, we found higher levels of the dietary odd-chain saturated fatty acids (OCFAs) pentadecanoic acid (C15:0) and heptadecanoic acid (C17:0) in beef than in the soy-based alternative. These compounds are believed to exert their beneficial effects by attenuating inflammation, dyslipidemia, and cell fibrosis 23 , and increased dietary intake is associated with a lower risk of metabolic disease 24,25 .…”
Section: Untargeted Metabolomics Of Plant-based Meat and Beefmentioning
confidence: 99%
“…Despite increases in risk factors, particularly LDL, preclinical rodent models employing coconut oil have failed to observe expected atherogenic 25,26 and diabetogenic 27 phenotypes. Both clinical trial 28 and observational epidemiological investigations 29,30 have suggested beneficial cardiometabolic effects of C12:0 relative to other saturated fatty acids. Such observations are consistent with pleiotropic effects of C12:0, though few have been described to date, apart from C12:0’s relative high oxidation rate in vivo 31 and ability to activate toll-like receptors at high concentrations in vitro 3234 .…”
Section: Introductionmentioning
confidence: 99%